Analysis of Indoor Luminous Environment and Power Generation by Roll Screen and Venetian Blind with PV Modules - In-Tae Kim, Seongkwan Hong; Choi, An-Seop (European Journal of Sustainable Development, 2017)
Venetian blind and roll screen are mainly used as a shading device because of the possibility of automatic control and simplicity of use. Venetian blind, in particular, can control the sunlight using slat rotation as well as up / down control. On the other hand, roll screen can control the direct sunlight inflow through up / down control. Such shading devices can also be used to generate electricity utilizing direct sunlight on them. This study aims to develop an optimal control method for generating electricity in terms of energy production while simultaneously blocking direct sunlight inflow in terms of occupant comfort using a shading device. In this study, we compare and analyze the change of the indoor luminous environment through appropriate control method for each shading device and power generation with attached PV modules. Keywords: Photovoltaic, Luminous environment, Power Generation, Venetian blinds, Roll screens, Shading device